2014
DOI: 10.1093/jrr/rrt142
|View full text |Cite
|
Sign up to set email alerts
|

3-Methyl pyruvate enhances radiosensitivity through increasing mitochondria-derived reactive oxygen species in tumor cell lines

Abstract: Considerable interest has recently been focused on the special characteristics of cancer metabolism, and several drugs designed to modulate cancer metabolism have been tested as potential anticancer agents. To date, however, very few studies have been conducted to investigate the combined effects of anticancer drugs and radiotherapy. In this study, to evaluate the role of mitochondria-derived reactive oxygen species (ROS) in the radiation-induced cell death of tumor cells, we have examined the effect of 3-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…Intracellular oxidative stress was evaluated by DCFDA staining, as reported [ 10 ]. Cells were treated with 0–1,000 μM SAS for 24 h. After SAS treatment, cells were stained with 20 μM DCFDA for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular oxidative stress was evaluated by DCFDA staining, as reported [ 10 ]. Cells were treated with 0–1,000 μM SAS for 24 h. After SAS treatment, cells were stained with 20 μM DCFDA for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the cytotoxicity induced by cisplatin alone, enhanced cytotoxicity was observed when cisplatin was delivered to mitochondria of chemoresistant A2780/CP70 cells by nanoparticles (NP); the cisplatin-nanoparticle combination decreased mtDNA levels and mitochondrial function [8]. In contrast, 3-methyl pyruvate, an activating agent for mitochondrial ETC, enhances radiosensitivity by increasing mitochondria-derived ROS levels in human lung carcinoma A549 cells and murine squamous carcinoma SCCVII cells [9]. These reports strongly suggested mitochondria as novel targets for radiation and chemotherapy in tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Such specificity for MC-I caused its uptake to be uninfluenced by inflammation caused by IR in the current study and as observed by microglia in the brain after ischemic damage [ 9 ]. The patterns of delayed and protracted uptake of 18 F-BCPP-EF closely resembled those of mitochondrial ROS production after irradiation in a variety of cell lines [ 5 , 20 , 21 ]. Likewise, the current study disclosed a highly significant positive correlation between 18 F-BCPP-EF uptake and radiation dose and its efficacy early after IR.…”
Section: Discussionmentioning
confidence: 86%